Strategies for grouping and remembering employed by educable mentally retarded children - Siega, Queenie Pajao; Sison, Waldetrudes Montojo (Quezon City College of Education, University of the Philippines Diliman, 1977)
This study was made to investigate the kinds of grouping strategies generated by educable mentally retarded children in a sorting task and the effect of these strategies on their recall and clustering performance. The subjects were made to sort an array of pictures that can be categorically grouped. A brief recall period followed. Results showed that majority of educable retarded children used the low level grouping strategies. Furthermore, they scored low in their recall and clustering. It was suggested that training programs should be developed to improve the conceptual skills of mentally retarded children, specifically, in their ability to see the association relationships between items in learning tasks.
Vita.
Thesis (Master of Arts in Teaching Special Education - Mental retardation)--University of the Philippines, Diliman.
Keywords: Children with mental disabilities -- Psychological testing -- Philippines; Children with mental disabilities -- Education -- Philippines; Mental retardation -- Philippines; Special education -- Philippines -- Makati City